Etyczne aspekty personalizowania treści w środowisku cyfrowym - Modrzejewska, Monika (Annales. Etyka w Życiu Gospodarczym, 2019)
Nowadays, the Internet fulfils multiple functions: it supplies us with information and entertainment, and it is sometimes all the social life we have. Typing any phrase into Google – the most popular Internet search engine – will give you thousands of answers in just a second. However trivial or important the question is, Google will come up with numerous search results. Internet users hardly ever stop to think how a content search list works and how the choice of what they see on their computer screen has been made for them. Hardly anybody knows that entering the same words in the search engine will bring different search results for different users. For every person browsing Google, the search engine will return expert interviews, press articles, scientific publications, etc. – but the answer to the search question will be biased, and can differ substantially for different users. What is at work here is the web personalization mechanism, which involves changes in the Google Search Algorithm depending on the place, time, and other circumstances of the question asked, as well as any past searches of the user. The same mechanism can be observed in Facebook’s news feed, which only serves us selective information. In the end, we all end up closed in a filter bubble. At the end of the day, in exchange for user-friendly Internet and our unyielding faith in technology, we pay the ultimate price – our freedom.